2008
DOI: 10.1111/j.1651-2227.2008.00990.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term non‐invasive positive airway pressure ventilation in infants

Abstract: NIV can be successfully and safely used in infants with prolonged life-threatening ventilatory failure, potentially avoiding intubation and tracheotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…To the best of our knowledge, we are reporting on the largest cohort of children initiated on NiPPV at less than 1 year of age. Similar to the Markstrom and Bach studies, we found that NiPPV was effective; there was a significant improvement in PaCO 2 levels in all patients after the initiation of NiPPV . No deaths were attributable to equipment failure in our cohort which is another significant finding.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…To the best of our knowledge, we are reporting on the largest cohort of children initiated on NiPPV at less than 1 year of age. Similar to the Markstrom and Bach studies, we found that NiPPV was effective; there was a significant improvement in PaCO 2 levels in all patients after the initiation of NiPPV . No deaths were attributable to equipment failure in our cohort which is another significant finding.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the Markstrom and Bach studies, we found that NiPPV was effective; there was a significant improvement in PaCO 2 levels in all patients after the initiation of NiPPV. 21,22 No deaths were attributable to equipment failure in our cohort which is another significant finding.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations